Pergeseran Nilai Budaya Matrilineal pada Perempuan Lanjut Usia di Minangkabau: Studi pada 2 Panti Sosial Werdha di Sumatera Barat - Irsyadunnas; Nurmahmi; Nailurrahmi (LP2M UIN Sunan Kalijaga, 2022)
This article analyzes the phenomenon of Minang elderly women who become residents of panti sosial as a result of the shift in Matrilineal traditional values in the life of the Minang community. The purpose of this article is to analyze what traditional values have shifted, their causes and impacts. This study used a qualitative approach, data collection was carried out through interview, observation, and documentation techniques. The data were analyzed using the principles of qualitative data analysis from Miles and Huberman. The results show that there has been a shift in Matrilineal traditional values in the phenomenon of Minang elderly women who are residents of the Panti Werdha, namely the value of children's responsibility to their parents, the value of the meaning of life for Minang elderly women, the value of togetherness and the value of leadership in Bundo Kanduang. The cause is due to several factors, namely migration, busyness, economy and lack of understanding of Minang youth about customs and religion. Meanwhile, the impact is the fading of the sense of kinship, ethnicity and even humanity of every family member, especially children. So that the Minang elderly women in the Panti Werdha feel they are not respected, excluded, and even become a burden in the family. [Artikel ini menganalisis tentang fenomena perempuan lansia Minang yang menjadi penghuni panti sosial sebagai akibat terjadinya pergeseran nilai adat Matrilineal dalam kehidupan masyarakat Minang. Tujuan artikel ini adalah untuk menganalisis apa saja nilai adat yang telah mengalami pergeseran, penyebab dan dampaknya. Penelitian ini menggunakan pendekatan kualitatif, pengumpulan data dilakukan melalui teknik wawancara, observasi, dan dokumentasi. Datanya dianalisis dengan prinsip-prinsip analisis data kualitatif dari Miles dan Huberman. Hasil penelitian menunjukkan bahwa telah terjadi pergeseran nilai adat Matrilineal dalam fenomena perempuan lansia Minang yang menjadi penghuni Panti Werdha, yaitu nilai tanggungjawab anak terhadap orangtuanya, nilai tentang makna hidup bagi perempuan lansia Minang, nilai kebersamaan dan nilai kepemimpinan Bundo Kanduang. Adapun penyebabnya adalah karena beberapa faktor yaitu faktor merantau, kesibukan, ekonomi dan kurangnya pemahaman anak muda Minang tentang adat dan agama. Sedangkan dampaknya adalah semakin memudarkan rasa kekeluargaan, kesukuan dan bahkan kemanusiaan dari setiap anggota keluarga terutama anak. Sehingga para perempuan lansia Minang di Panti Werdha tersebut merasa tidak dihormati, tersisihkan, bahkan menjadi beban dalam keluarga.]